Proteinase-Mediated Macrophage Signaling in Psoriatic Arthritis - Abji, Fatima; Rasti, Mozhgan; Gómez-Aristizábal, Alejandro; Muytjens, Carla; Saifeddine, Mahmoud; Mihara, Koichiro; Motahhari, Majid; Gandhi, Rajiv; Viswanathan, Sowmya; Hollenberg, Morley D.; Oikonomopoulou, Katerina; Chandran, Vinod (Frontiers in Immunology, 2021)
Objective: Multiple proteinases are present in the synovial fluid (SF) of an arthritic joint. We aimed to identify inflammatory cell populations present in psoriatic arthritis (PsA) SF in comparison to osteoarthritis (OA) and rheumatoid arthritis (RA) and characterize active SF serine proteinases and their proteinase-activated receptor 2 (PAR2) signalling function. Methods: Flow cytometry was used to characterize SF cells from PsA, RA, OA patients; PsA SF was further characterized by single cell 3’-RNA-sequencing. Active serine proteinases were identified through cleavage of fluorogenic trypsin- and chymotrypsin-like substrates, activity-based probe analysis and functional proteomics. Fluo-4 AM was used to monitor intracellular calcium cell signalling. Cytokine expression was evaluated using a multiplex Luminex panel. Results: PsA SF cells were dominated by monocytes/macrophages, which consisted of three populations representing the classical, non-classical and intermediate cells. When comparing PsA with OA/RA, the classical monocytes/macrophages were reduced whilst the intermediate population was increased. Trypsin-like serine proteinase activity with preference for D-Val-Leu-Lys-Aminomethylcoumarin was elevated in RA and PsA SF compared to OA, while chymotrypsin-like activity was elevated in RA compared to PsA. PAR2 cell surface expression was elevated in OA vs. PsA/RA SF monocytes/macrophages, particularly in the intermediate population. PAR2 activation and inhibition was observed in primary PsA monocytes/macrophages with significant production of MCP-1. Tryptase-6 was identified as an active proteinase in SF that triggers calcium signalling partially via PAR2. Conclusion: PAR2 and its activating proteinases, including tryptase-6, can be important mediators of inflammatory signalling in PsA. Components within this proteinase-receptor axis may represent novel therapeutic targets.